2009
DOI: 10.1111/j.1468-1331.2009.02784.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of rapid repetitive finger movements and visual reaction time in patients with essential tremor

Abstract: Patients with ET showed impaired motor performance, at least in some tasks, such as rapid repetitive finger movements (finger tapping and frequency) and visual reaction time (impairment was not related with tremor severity). This probably means that patients with ET have some degree of bradykinesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
3
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
1
49
3
5
Order By: Relevance
“…PS speed in our healthy subjects was correlated with that for FT in the right (dominant), but not in the left hand. Despite this correlation, patients with Parkinson's disease [54] or essential tremor [55] have shown a worse performance for the FT tasks than for PS.…”
Section: Discussionmentioning
confidence: 94%
“…PS speed in our healthy subjects was correlated with that for FT in the right (dominant), but not in the left hand. Despite this correlation, patients with Parkinson's disease [54] or essential tremor [55] have shown a worse performance for the FT tasks than for PS.…”
Section: Discussionmentioning
confidence: 94%
“…24 The weight of emerging evidence is indicating that, aside from motor manifestations, ET is also associated with a number of nonmotor manifestations, including cognitive deficits, 5 dementia, 6 depressive symptoms, 7 changes in sleep patterns, 8 changes in visual reaction time, 9 and hearing impairment. 10,11 Clinical and imaging studies point to cerebellar involvement, and the tremor is thought to be mediated by a neuronal loop involving cerebello-thalamo-cortical pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Support for this suggestion that the execution of rhythmic behavior is unaffected by ET has been provided by Ozekmekci et al (2005), who found that individuals with ET and controls did not perform differently a sequential-tapping task. Whereas the previous research suggested that initiation is largely unaffected in ET, other studies did show that both movement initiation and execution were affected (Montgomery, Baker, Lyons, & Koller, 2000;Jimenez-Jimenez et al, 2010). For example, Montgomery and colleagues showed that the reaction time and movement velocity of a wrist flexion and extension task were slower for individuals with ET and PD.…”
mentioning
confidence: 86%
“…For example, Montgomery and colleagues showed that the reaction time and movement velocity of a wrist flexion and extension task were slower for individuals with ET and PD. Also, JimenezJimenez and colleagues showed that individuals with ET exhibited impairments in rapid repetitive finger movements and visual reaction time tasks (Jimenez-Jimenez et al, 2010), whereas Farkas, Szirmai, and Kamondi (2006) showed higher variability in individuals with ET than in controls when they rhythmically tapped their fingers and made alternating hand movements (Farkas et al, 2006). In general, it can be concluded that individuals with ET have a measurable disability with time-based upper-extremity function (Heroux, Parisi, Larocerie-Salgado, & Norman, 2006).…”
mentioning
confidence: 99%